Savings banks and cooperative banks in Europe - Dilek Bülbül; Reinhard H. Schmidt; Ulrich Schüwer (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
Until about 25 years ago, almost all European countries had a so-called three pillar banking system comprising private banks, (public) savings banks and (mutual) cooperative banks. Since that time, several European countries have implemented far-reaching changes in their banking systems, which have more than anything else affected the two pillars of the savings and cooperative banks. The article describes the most important changes in Germany, Austria, France, Italy and Spain and characterizes the former and the current roles of savings banks and cooperative banks in these countries. A particular focus is placed on the German case, which is almost unique in so far as the German savings banks and cooperative banks have maintained most of their traditional features. The article concludes with a plea for diversity of institutional forms of banks and argues that it is important to safeguard the strengths of those types of banks that do not conform to the model of a large shareholder-oriented commercial bank.
urn:nbn:de:hebis:30:3-315535
Keywords: 330